(untitled) (Italian Journal of Public Health, 2008)
Background: IgE-mediated allergic disease may clinically manifest itself with either a single symptom or a multisymptomatic disease involving different organs. In this work we investigated whether gender and age of the patients and reactivity to specific allergens are related to different clinical presentations of IgE-mediated allergic disease, considering in particular eye-conjunctival and cutaneous symptoms, alone or in combination. Methods: Epidemiological and clinical data related to patients of the Local Health Unit of Torino and Alessandria were collected. Measuring of specific Immunoglobulin E (IgE) was carried out by using allergenic extracts and by the employment of the chemiluminescence method. Clinical outcomes were the presence of eye-conjunctival, cutaneous (with also other symptom), and only cutaneous symptoms. The covariates under study were the type of allergen (mite, epithelium, poaceae, food, trees and grasses), number and localisation of the allergic reactions, gender, age over 30 years. For each clinical outcome, a logistic regression analysis was performed. Statistical significance was set at p < 0.05. Results: 844 patients with allergic problems (clinical manifestations of allergic disease) entered the study. We found that exposure to epithelium [OR=3,61; IC 95% (2,17; 6,00)], poaceae [OR=2,24; IC 95% (1,46; 3,42)], grasses [OR=2,06; IC 95% (1.35; 3,14)] and age over 30 years [OR=2,05; IC 95% (1,35; 3,13)] are risk factors for the development of eye-conjunctival symptoms. With regard to cutaneous allergic reactions, exposure to mite [OR=1,49; IC 95% (1,07; 2,08)], food [OR=4,16; IC 95% (3,01; 5,75)] and multidistrict symptoms [OR=3,63; IC 95% (2,54; 5,20)] should be risk factors. Instead, considering only cutaneous reactions, possible risk factor is the exposure to food [OR=3,58; IC 95% (2,54; 5,03)]. The exposure to trees is associated with a reduction of the likelihood to have cutaneous [OR=0,45; IC 95% (0,26; 0,76)] and only cutaneous reactions [OR=0,24; IC 95% (0,11; 0,53)]. For only cutaneous symptoms, a reduction in probability is present for the exposure to the grasses [OR=0,60; IC 95% (0,38; 0,94)] too. Conclusions: The study highlighted significant associations between subgroups of allergens and specific symptoms. As a consequence, in the presence of cutaneous symptoms, IgE tests could be restricted to mite and food, and to epithelium, poaceae and grasses in the presence of oculo-conjunctival symptoms.